2005
DOI: 10.1002/ijc.21126
|View full text |Cite
|
Sign up to set email alerts
|

Folate receptor-targeted immunotherapy: Induction of humoral and cellular immunity against hapten-decorated cancer cells

Abstract: We previously exploited the frequent overexpression of folate receptors on cancer cells to decorate malignant cell surfaces selectively with folate-hapten conjugates. In antihapten-immunized hosts, this targeted localization of foreign haptens to tumor cells led to rapid accumulation of autologous antihapten IgG, which in turn yielded potent antitumor activity upon stimulation with cytokines (IL-2, IFN-a). In an effort to understand the effector mechanisms responsible for tumor regression, we have now investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 45 publications
5
88
0
Order By: Relevance
“…3C) revealed that although systemically given 3 H-folate-FITC could localize quickly to a folate receptor -positive tumor, the majority of the compound was simultaneously bound to anti-FITC antibody in the plasma. We have previously observed that folate-FITC present in vast excess over anti-FITC antibody may actually avert the ''anchoring'' of anti-FITC antibody to folate receptor -positive tumor (7,8). In an effort to consolidate our findings and to further enhance antitumor activity, immunized mice bearing s.c. M109 tumors (f100 mm 3 ) were given a 3-week regimen (dosing five times per week) consisting of folate-FITC at three dose levels (500, 2,000, and 5,000 nmol/kg), alone or in combination with IL-2 and IFN-a.…”
Section: Therapeutic Dosing Effect Of Folate-fitc At a Fixed Cytokinementioning
confidence: 74%
See 4 more Smart Citations
“…3C) revealed that although systemically given 3 H-folate-FITC could localize quickly to a folate receptor -positive tumor, the majority of the compound was simultaneously bound to anti-FITC antibody in the plasma. We have previously observed that folate-FITC present in vast excess over anti-FITC antibody may actually avert the ''anchoring'' of anti-FITC antibody to folate receptor -positive tumor (7,8). In an effort to consolidate our findings and to further enhance antitumor activity, immunized mice bearing s.c. M109 tumors (f100 mm 3 ) were given a 3-week regimen (dosing five times per week) consisting of folate-FITC at three dose levels (500, 2,000, and 5,000 nmol/kg), alone or in combination with IL-2 and IFN-a.…”
Section: Therapeutic Dosing Effect Of Folate-fitc At a Fixed Cytokinementioning
confidence: 74%
“…Consequently, folate-FITC can promote antibody-dependent cellular cytotoxicity, phagocytosis, and perhaps T cell -mediated tumor cell killing (8). In the tumor destruction process, however, costimulation with the proinflammatory cytokines IL-2 and IFN-a seemed to be important in promoting a more effective and longlasting antitumor response (8). Because high cytokine doses are often associated with unwanted toxicity, we investigated the effect of using lower doses of IL-2 and IFN-a in support of a fixed dosing regimen of folate-FITC.…”
Section: Therapeutic Dosing Effect Of Cytokines At a Fixed Dose Of Fomentioning
confidence: 99%
See 3 more Smart Citations